Respostas
respondido por:
31
Sabemos que
(x-y)²= x² - 2xy + y²
7²= x² + y² -2xy
x² + y² -2xy = 49
x² + y²- 2.60 = 49
x² + y² = 49 +120
x² + y² = 169
(x-y)²= x² - 2xy + y²
7²= x² + y² -2xy
x² + y² -2xy = 49
x² + y²- 2.60 = 49
x² + y² = 49 +120
x² + y² = 169
strshine:
ajuda lá nos polinômios Alexandre! http://brainly.com.br/tarefa/6814295?utm_source=android&utm_medium=share&utm_campaign=question se souber, e não for encomodar!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás